Combined provision of primary frequency regulation from Vehicle-to-Grid (V2G) capable electric vehicles and community-scale heat pump. (September 2020) - Meesenburg, Wiebke; Thingvad, Andreas; Elmegaard, Brian; Marinelli, Mattia
Abstract: A combined delivery of frequency containment reserve (FCR) from a fleet of electric vehicles (EVs) and a large-scale heat pump is proposed to exploit synergies between the fast regulating batteries and the large heat storage capacity of the thermal system. The feasibility of the proposed strategy is assessed with a state of charge model for the EVs delivering FCR, based on one year of system frequency measurements including the conversion losses in the charger and a dynamic model of the heat pump system. Both models were previously validated against experimental data. The proposed operation of the EVs was experimentally validated as part of this study. The heat pump offsets the energy content of the frequency deviations for 25 EVs and thereby enables them to bid a larger power capacity on the FCR market without violating energy constraints of the battery capacity. For the case of 2018 an additional income from capacity and power price payments was obtained that could not be generated by the EVs or the heat pump alone. This synergy effect was shown to be highly dependent on the achievable capacity payments, which were relatively high for the 2018 case. Highlights: Different demand side units deliver a combined frequency regulation service. Fast-regulating EVs with small storage capacity enable primary frequency regulation. Heat pump with heat storage enables EVs to bid larger capacity into reserve market. Frequency response from electric vehicles is experimentally validated. Economic synergy effect may be obtained by combined service provision.